SULHA THEOLOGICAL FOUNDATION: TRACING KEY CONCEPTS OF RECONCILIATION IN WORLDVIEW OF ISLAM - Abdullah Rizal Maulana (UNIDA Gontor, 2019)
Sulha is one well-known method of reconciliation owned by Palestinian Society. Historically, Palestinian utilized it to accommodate two hostile tribes in families in a peacemaking process to prevent conflict escalate to the higher level. As a featured local way to harmonize its people, Palestinian have applied Sulha since the very beginning of Palestinian Civilization to nowadays. Unavoidably, Sectarian collision in Palestine always involves three major religious worshippers within the area: Islam, Christian, and Jewish. Considering its vital position in the Palestinian communities, there has been a lot of researches discussing Sulha as an inseparable element of reconciliation method needed by Palestinians to confront Israelis in particular. Sulha, in another word, plays such a crucial role to find the peacemaking process of Palestinian in a better way. Several tasks remaining, however, to validate and strengthen Sulha as a unique method of reconciliation of Palestinian. After reading several kinds of literature, I believe that Sulha is able to be understood in Worldview of Islam; there are numbers of key concepts associated with Sulha in major Islamic literature: mainly al-Qur'an and Hadith. For instance,Hospitality, Repentance, and Forgiveness. This paper will discuss the interrelation of these keywords to Sulha based on the critical reading of ancient literature of Islam and how it should be implemented by Palestinians to enhance and advance Sulha as a method of conflict resolution. Finally, the research question in this article that will be discussed and answered is: “What are the featured key concepts of Sulha in Worldview of Islam and how it should be implemented by Palestinians?”